2019
DOI: 10.3389/fcimb.2019.00241
|View full text |Cite
|
Sign up to set email alerts
|

Innate Immune Recognition: An Issue More Complex Than Expected

Abstract: Primary interaction of an intracellular bacterium with its host cell is initiated by activation of multiple signaling pathways in response to bacterium recognition itself or as cellular responses to stress induced by the bacterium. The leading molecules in these processes are cell surface membrane receptors as well as cytosolic pattern recognition receptors recognizing pathogen-associated molecular patterns or damage-associated molecular patterns induced by the invading bacterium. In this review, we demonstrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
44
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 243 publications
(282 reference statements)
0
44
0
Order By: Relevance
“…Both innate immunity and adaptive immunity are involved in the progression of T1DM (12)(13)(14). Innate immunity, which serves as the first line of defense against an exogenous attack by bacteria, viruses, and fungi, is a relatively conserved immune response compared with adaptive immunity (15,16). Previous studies have confirmed that the innate immune system exerts its effect via highly conserved PRRs (pattern-recognition receptors) to initiate innate inflammatory responses to both exogenous and endogenous trigger factors and further activate adaptive immunity (16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both innate immunity and adaptive immunity are involved in the progression of T1DM (12)(13)(14). Innate immunity, which serves as the first line of defense against an exogenous attack by bacteria, viruses, and fungi, is a relatively conserved immune response compared with adaptive immunity (15,16). Previous studies have confirmed that the innate immune system exerts its effect via highly conserved PRRs (pattern-recognition receptors) to initiate innate inflammatory responses to both exogenous and endogenous trigger factors and further activate adaptive immunity (16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%
“…Innate immunity, which serves as the first line of defense against an exogenous attack by bacteria, viruses, and fungi, is a relatively conserved immune response compared with adaptive immunity ( 15 , 16 ). Previous studies have confirmed that the innate immune system exerts its effect via highly conserved PRRs (pattern-recognition receptors) to initiate innate inflammatory responses to both exogenous and endogenous trigger factors and further activate adaptive immunity ( 16 18 ). Upon the recognition of DAMPs and PAMPs, which are associated with cellular stress and microbial pathogens, PRRs promote the secretion of proinflammatory cytokines by inducing either non-transcriptional or transcriptional innate immune responses ( 19 , 20 ).…”
Section: Introductionmentioning
confidence: 99%
“…Just as important is that bacterial pathogens have evolved to modulate various biochemical and cellular functions in host cells to render them permissive for bacterial proliferation [ 9 ]. Intracellular pathogens have evolved to adapt to the intracellular environment within vacuoles that are not trafficked properly within the endosomal lysosomal degradation pathway and evade various aspects of the innate immune response [ 10 , 11 , 12 ]. The cellular pathways manipulated by pathogen are involved in numerous aspects of the host cell biology, such as signaling, autophagy, apoptosis and inflammasomes [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the ability of virus to escape or antagonize IFN reaction to a certain extent determines the fate of virus and host in the future. Almost all the viruses, both DNA virus and RNA virus, have developed multifarious strategies to interfere with the synthesis of IFNs or IFN receptor signaling pathway, including reducing the expression of type I IFN receptor mRNA, blocking the posttranslation modification, degrading the IFN receptor, and utilizing the virus bait protein to bind to type I interferon to prevent the receptor from recognizing interferon and inhibiting JAK/STAT signal, further regulating the antiviral function of ISG products [43,44].…”
Section: Introductionmentioning
confidence: 99%